Poverty, food insecurity, and social protection during COVID-19 in Myanmar: Combined evidence from a household telephone survey and micro-simulations - Headey, Derek D.; Oo, Than Zaw; Mahrt, Kristi; Diao, Xinshen; Goudet, Sophie; Lambrecht, Isabel B. (International Food Policy Research Institute, 2020)
This study assesses the welfare impacts of COVID-19 on households in Myanmar by combining recent high-frequency telephone survey evidence for two specific rural and urban geographies with national-level survey-based simulations designed to assess ex-ante impacts on poverty with differing amounts of targeted cash transfers. The first source of evidence – the COVID-19 Rural and Urban Food Security Survey (C19- RUFSS) – consists of four rounds of monthly data collected from a sample of over 2,000 households, all with young children or pregnant mothers, divided evenly between urban and peri-urban Yangon and the rural Dry Zone. This survey sheds light on household incomes prior to COVID-19 (January 2020), incomes and food security status soon after the first COVID-19 wave (June 2020), the gradual economic recovery thereafter (July and August 2020), and the start of the second COVID-19 wave in September and October 2020. This survey gives timely and high-quality evidence on the recent welfare impacts of COVID-19 for two important geographies and for households that are nutritionally highly vulnerable to shocks due to the presence of very young children or pregnant mothers. However, the relatively narrow geographic and demographic focus of this telephone survey and the need for forecasting the poverty impacts of COVID-19 into 2021 prompt us to explore simulationbased evidence derived by applying parameter shocks to household models developed from nationally representative household survey data collected prior to COVID-19, the 2015 Myanmar Poverty and Living Conditions Survey (MPLCS). By realistically simulating the kinds of disruptions imposed on Myanmar’s economy by both international forces, e.g., lower agricultural exports and workers’ remittances, and domestic COVID-19 prevention measures. e.g., stay-at-home orders and temporary business closures, we not only can predict the impacts of COVID-19 on household poverty at the rural, urban, and national levels, but also can assess the further benefits to household welfare of social protection in the form of monthly household cash transfers of different magnitudes. Combined, these two sources of evidence yield insights on both the on-the-ground impacts of COVID-19 in recent months and the potential poverty reduction impacts of social protection measures in the coming year. We conclude the study with a discussion of the policy implications of these findings.